Detection of total hip arthroplasties at airport security checkpoints – how do updated security measures affect patients?. Issue 2 (March 2018) - Issa, Kimona; Pierce, Todd P.; Gwam, Chukwuweieke; Festa, Anthony; Scillia, Anthony J.; Mont, Michael A.
Introduction: There have been historical reports on the experiences of patients with total hip arthroplasty (THA) passing through standard metal detectors at airports. The purpose of this study was to analyse those who had recently passed through airport security and the incidence of: (i) triggering of the alarm; (ii) extra security searches; and (iii) perceived inconvenience. Methods: A questionnaire was given to 125 patients with a THA during a follow-up appointment. Those who had passed through airport security after January 2014 met inclusion criteria. A survey was administered that addressed the number of encounters with airport security, frequency of metal detector activation, additional screening procedures utilised, whether security officials required prosthesis documentation, and perceived inconvenience. Results: 51 patients met inclusion criteria. 10 patients (20%) reported triggered security scanners. 4 of the 10 patients stated they had surgical hardware elsewhere in the body. 13 of the 51 patients (25%) believed that having their THA increased the inconvenience of traveling. This is different from the historical cohort with standard metal detectors which patients reported a greater incidence of alarm triggering (n = 120 of 143; p = 0.0001) and perceived inconvenience (n = 99 of 143; p = 0.0001). Discussions: The percentage of patients who have THA triggering security alarms has decreased. Furthermore, the number of patients who feel that their prosthesis caused traveling inconvenience has decreased. We feel that this decrease in alarms triggered and improved perceptions about inconvenience are related to the increased usage of new technology.